Staphylococcus aureus and Methicillin Resistant S. aureus in Nepalese Primates: Resistance to Antimicrobials, Virulence, and Genetic Lineages - Marilyn C. Roberts; Prabhu Raj Joshi; Stefan Monecke; Ralf Ehricht; Elke Müller; Darius Gawlik; Celia Diezel; Sascha D. Braun; Saroj Paudel; Mahesh Acharya; Laxman Khanal; Narayan P. Koju; et al. (MDPI AG, 2020)
Staphylococcus aureus is a ubiquitous pathogen and colonizer in humans and animals. There are few studies on the molecular epidemiology of S. aureus in wild monkeys and apes. S. aureus carriage in rhesus macaques (Macaca mulatta) and Assam macaques (Macaca assamensis) is a species that has not previously been sampled and lives in remote environments with limited human contact. Forty Staphylococcus aureus isolates including 33 methicillin-susceptible S. aureus (MSSA) and seven methicillin-resistant S. aureus (MRSA) were characterized. Thirty-four isolates were from rhesus macaques and six isolates (five MSSA, one MRSA) were from Assam macaques. Isolates were characterized using StaphyType DNA microarrays. Five of the MRSA including one from Assam macaque were CC22 MRSA-IV (PVL+/tst+), which is a strain previously identified in Nepalese rhesus. One MRSA each were CC6 MRSA-IV and CC772 MRSA-V (PVL+). One MSSA each belonged to CC15, CC96, and CC2990. Six MRSA isolates carried the blaZ, while ten known CC isolates (seven MRSA, three MSSA) carried a variety of genes including aacA-aphD, aphA3, erm(C), mph(C), dfrA, msrA, and/or sat genes. The other 30 MSSA isolates belonged to 17 novel clonal complexes, carried no antibiotic resistance genes, lacked Panton-Valentine Leukocidin (PVL), and most examined exotoxin genes. Four clonal complexes carried egc enterotoxin genes, and four harbored edinB, which is an exfoliative toxin homologue.